Spinal Epidural Abscess – A Rare Complication of Inflammatory Bowel Disease - Carl J Brown; Hussein Jaffer; Nasir Jaffer; Claude Burul; Robin S McLeod (Canadian Journal of Gastroenterology)
Spinal epidural abscess is an uncommon but highly morbid illness. While it usually afflicts older, immunocompromised patients, this condition has been reported as a result of intestinal perforation in the setting of inflammatory bowel disease. Two cases of spinal epidural abscess in patients with inflammatory bowel disease are reported: one in a patient with Crohn’s disease and one in a patient with ulcerative colitis after restorative proctocolectomy.